The Influence of Entrepreneurship Education in Growing Students' Interest in Become Entrepreneurs - Hardi Utomo; Media Rachmawati (Journal of Economics and Management Scienties, 2023)
Advances in technology and science have contributed to encouraging entrepreneurial practices, leading to various new product and service inventions for consumers. This, of course, opens up new job opportunities and markets, and in the long term, will be able to create business growth in various sectors. This study aims to describe and analyze facts with the correct interpretation of efforts to improve soft student skills through entrepreneurship education. So, the most appropriate research approach is a qualitative approach. After attending entrepreneurship education, students generally have the courage and self-confidence to increase and are more confident and vital to enter the world of entrepreneurship/business.